Virus diseases of poppy (Papaver somniferum L.) and some other species of the Papaveraceae family - a review - Darina Kubelková; Josef Špak (Plant Protection Science, 1999)
Opium poppy (Papaver somniferum L.) is described in the literature as a natural host of turnip mosaic virus, bean yellow mosaic virus, beet yellows virus and beet mosaic virus, and experimental host of plum pox virus. P. orientale L., a natural host of beet curly top virus, was successfully infected with turnip mosaic virus and cucumber mosaic virus, and P. dubium L. with turnip mosaic virus. P. rhoeas L. is a natural host of turnip mosaic virus, and artificial host of beet yellows, plum pox and cucumber mosaic viruses. P. nudicaule is reported as a natural host of beet curly top, tomato spotted wilt viruses and turnip mosaic, experimentally it was infected with turnip mosaic virus. Eschscholtzia californica Cham. is described as a natural host of aster yellows phytoplasma, and experimental host of bean yellow mosaic virus. In the Czech Republic, only turnip mosaic virus was reliably identified in naturally infected P. somniferum.